“Soluble Tissue Factor” in the 21st Century: Definitions, Biochemistry, and Pathophysiological Role in Thrombus Formation - Bogdanov, Vladimir Y.; Versteeg, Henri H. (Seminars in Thrombosis and Hemostasis, 2015)
Tissue factor (TF), the main trigger of blood coagulation, is essential for normal hemostasis. Over the past 20 years, heightened intravascular levels and activity of TF have been increasingly perceived as an entity that significantly contributes to venous as well as arterial thrombosis. Various forms of the TF protein in the circulation have been described and proposed to be thrombogenic. Aside from cell and vessel wall-associated TF, several forms of non–cell-associated TF circulate in plasma and may serve as a causative factor in thrombosis. At the present time, no firm consensus exists regarding the extent, the vascular setting(s), and/or the mechanisms by which such TF forms contribute to thrombus initiation and propagation. Here, we summarize the existing paradigms and recent, sometimes paradigm-shifting findings elucidating the structural, mechanistic, and pathophysiological characteristics of plasma-borne TF.
Keywords: tissue factor; thrombosis; microparticle; alternative splicing; atherosclerosis